'I would never have done it if it hadn't been digital': a qualitative study on patients' experiences of a digital management programme for hip and knee osteoarthritis in Sweden. Issue 5 (24th May 2019) - Cronström, Anna; Dahlberg, Leif E; Nero, Håkan; Ericson, Jennifer; Hammarlund, Catharina Sjödahl
Abstract : Objectives: To investigate the experiences of a digital management programme for hip and knee osteoarthritis (OA), including education and exercises as well as an option to chat with an assigned physical therapist for feedback, questions and support. Setting: This study was conducted at a regional hospital in the southern part of Sweden. Methods: Nineteen patients (10 women), median age of 66 (q1–q3, 57–71) years, with confirmed hip or knee OA were interviewed after completing their first 6 weeks in the programme, using a semistructured interview guide. The interviews were transcribed verbatim and were qualitatively analysed using systematic text condensation. Results: Three categories emerged during the interviews: (1) Management options for mitigating the consequences of OA; (2) Experiences of the digital programme and (3) Perceived effects of the digital programme over time. The participants had mostly positive experiences of the programme. Particularly important for these experiences were no waiting list, the flexibility of taking part in the programme with regards to location and time and the possibility to have daily contact with a physical therapist. These aspects were also emphasised as advantages compared with traditional care. Conclusions: Digital management of OA, including education and exercise, was experienced as a valid alternative to traditional treatment in enabling the implementation of OA guidelines in a wider community. Easy access, exercising at one's own convenience, flexible options, daily follow-up and support by a physical therapist were mentioned as the most important features. In addition, the results will contribute to further development and improvement of digital OA management programmes.